2004
DOI: 10.1007/s10120-004-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and risk of gastric cancer: a case-control study in Uruguay

Abstract: This study displayed consistent results from three different approaches. Concerning different food groups, stewed and processed meat are rich in salt; rice, tubers, and winter squash are sources of starch; and vegetables and fruits are rich in ascorbic acid and carotenoids. All these substances have been strongly related to gastric carcinogenesis. Furthermore, this study suggests that diets rich in vegetables and fruits and with low amounts of salty and starchy foods are recommendable for the prevention of gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
94
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 34 publications
(38 reference statements)
10
94
3
Order By: Relevance
“…Results from epidemiological studies on gastric cancer were inconsistent, with case-control ones suggesting, if any, a protective effect of coffee on gastric carcinogenesis [2][3][4][5], and some, but not all [1,2], cohort studies possibly suggesting an increased risk of gastric cancer in relation to coffee consumption [6][7][8]. However, none of the risk estimates provided by prospective studies were adjusted for several possible confounders, including tobacco smoking.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Results from epidemiological studies on gastric cancer were inconsistent, with case-control ones suggesting, if any, a protective effect of coffee on gastric carcinogenesis [2][3][4][5], and some, but not all [1,2], cohort studies possibly suggesting an increased risk of gastric cancer in relation to coffee consumption [6][7][8]. However, none of the risk estimates provided by prospective studies were adjusted for several possible confounders, including tobacco smoking.…”
Section: Discussionmentioning
confidence: 85%
“…Black tea was inversely related to gastric cancer risk in case-control studies from India [11], Sweden [12], Poland [13], and Uruguay [5]. However, at least seven cohort studies from the USA [7,14], northern Europe [15,16], and Japan [1,17,18] found no clear association.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies have reported the correlation between diet and gastric cancer (Ngoan et al, 2002;Kelley and Duggan, 2003;De Stafani et al, 2004;Nan et al, 2005). It was shown that pickled, salted and fatty foods significantly enhanced the risk of cancer development.…”
Section: Diet and Its Role In Gastric Cancermentioning
confidence: 99%
“…Another study with 240 subjects also discovered that a high consumption of starchy foods such as rice; white bread; potatoes and tubers played a significant role in the development of this cancer. Further, it was also concluded that diets high in vegetables and fruits reduced the risk of developing stomach cancer (De Stafani et al, 2004).…”
Section: Diet and Its Role In Gastric Cancermentioning
confidence: 99%